A Case study of community empowerment in orang asli villages: Pos Yum and kampung Pendeq, Sungai Siput, Perak, Malaysia - Zal Hasmi Mohamad Roslan,; Nur Hasyareeda Hassan,; Siti Aishah Hasbullahh,; Norfarhan Mohd Assa'ad,; Mohd Shahrim Senik, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The 17 Sustainable Development Goals (SDGs) are at the heart of the 2030 agenda for sustainable development. This report focuses on the case study impact of Orang Asli Village in Pos Yum and Pendeq, Sungai Siput, Perak, Malaysia, as the outcome of the offroad Corporate Social Responsibility (CSR) activity organized by Persatuan Mahasiswa, Fakulti Sains dan Teknologi, UKM. The CSR activity was supported by Yayasan Food Bank Malaysia (YFBM), the charitable organization governed by a Board of Trustees that put an effort to reduce food waste from the manufacturer, wholesaler, hypermarket and hotel industry, sort and re-distribute it to the identified targeted B40 communities in higher learning institution (IPT), charity home, welfare centre and Program Perumahan Rakyat Termiskin (PPRT). This CSR program also received assistance from organizations such as the Department of Civil Defence Malaysia, Yayasan Dana Kita and Laboratory and Instrumentation Secretariat Faculty Science and Technology UKM (SMI FST UKM). The activities carried out during the CSR are aimed at looking at the menstrual poverty among Orang Asli and providing information on menstrual hygiene and awareness. Furthermore, it was discovered that Orang Asli needed help finding healthy food sources. Another issue is the spread of infectious diseases among the Orang Asli without sufficient education. Ineffective transport and infrastructure discourage parents from bringing their children to medical facilities, leading to infectious diseases. This indicates the urgency of locating missions and providing Orang Asli Village with a full range of action health services. Furthermore, it sparked a great deal of interest among students and non-governmental organizations to launch a new initiative to steer the future of these indigenous people in the direction of life to its fullest.